2014
DOI: 10.3892/etm.2014.1987
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine, Qing Ying Tang, ameliorates the severity of acute lung injury induced by severe acute pancreatitis in rats via the upregulation of aquaporin-1

Abstract: Aquaporin-1 (AQP-1) is expressed in lung endothelial cells and regulates water transport; thus, AQP-1 plays an important role in a number of edema-associated lung diseases. Qing Yin Tang (QYT), a traditional Chinese medicine, has been shown to effectively reduce the mortality rate of acute lung injury (ALI) induced by severe acute pancreatitis (SAP). The current study aimed to investigate the detailed mechanisms underlying the effects of QYT on ALI induced by SAP, particularly the effects on the expression lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
(33 reference statements)
1
17
0
Order By: Relevance
“…Many studies have demonstrated that emodin intervention could significantly decrease the production of serum amylase and inflammatory mediators/cytokines in lung tissues, such as TNF-α, IL-6 levels, as well as lower MPO activity. 18,26,27 DEX was a non-specific immune inhibitor, it inhibited gene synthesis of numerous inflammatory mediators and increased the synthesis of anti-inflammatory proteins, its good therapeutic benefit in SAP-associated ALI has been confirmed. 28,29 In this study, emodin and DEX have a similar effect on ALI, and there were no differences between them, which further demonstrated the effectiveness of emodin.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Many studies have demonstrated that emodin intervention could significantly decrease the production of serum amylase and inflammatory mediators/cytokines in lung tissues, such as TNF-α, IL-6 levels, as well as lower MPO activity. 18,26,27 DEX was a non-specific immune inhibitor, it inhibited gene synthesis of numerous inflammatory mediators and increased the synthesis of anti-inflammatory proteins, its good therapeutic benefit in SAP-associated ALI has been confirmed. 28,29 In this study, emodin and DEX have a similar effect on ALI, and there were no differences between them, which further demonstrated the effectiveness of emodin.…”
Section: Discussionmentioning
confidence: 97%
“…Emodin, derived from the traditional Chinese medicine, rhubarb, has a long history of use in anti‐inflammation. Many studies have demonstrated that emodin intervention could significantly decrease the production of serum amylase and inflammatory mediators/cytokines in lung tissues, such as TNF‐α, IL‐6 levels, as well as lower MPO activity . DEX was a non‐specific immune inhibitor, it inhibited gene synthesis of numerous inflammatory mediators and increased the synthesis of anti‐inflammatory proteins, its good therapeutic benefit in SAP‐associated ALI has been confirmed .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It can develop into acute respiratory distress syndrome (ARDS) without timely intervention. [1] Wu et al [2][3][4] reported that ALI is a kind of medium disease. The activation, invasion and massive release of infl ammatory mediators of neutrophils can cause damage to lung tissue and capillaries, thus aggravaing lung injury.…”
Section: Introductionmentioning
confidence: 99%